2022
DOI: 10.3389/fmicb.2022.934525
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Effects of Daily Antiseptic Treatment on Microbial Composition of Saliva-Grown Microcosm Biofilms and Selection of Resistant Phenotypes

Abstract: Antiseptics are widely used in dental practice and included in numerous over-the-counter oral care products. However, the effects of routine antiseptic use on microbial composition of oral biofilms and on the emergence of resistant phenotypes remain unclear. Microcosm biofilms were inoculated from saliva samples of four donors and cultured in the Amsterdam Active Attachment biofilm model for 3 days. Then, they were treated two times daily with chlorhexidine digluconate (CHX) or cetylpyridinium chloride (CPC) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…It must further be considered that it is still unclear whether the observed reductions of SARS-CoV-2 infectivity after gargling with mouthwashes containing CPC or other active ingredients can lead to clinically relevant reductions in the risk of transmission of SARS-CoV-2 ( Cieplik and Jakubovics 2022 ). Furthermore, it must be kept in mind that the frequent use of antiseptics may also exert some negative effects such as inducing potentially detrimental ecological shifts in the oral microbiota ( Mao et al 2022 ) or development of antiseptic resistance in oral bacteria ( Verspecht et al 2019 ; Auer et al 2022 ; Muehler et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It must further be considered that it is still unclear whether the observed reductions of SARS-CoV-2 infectivity after gargling with mouthwashes containing CPC or other active ingredients can lead to clinically relevant reductions in the risk of transmission of SARS-CoV-2 ( Cieplik and Jakubovics 2022 ). Furthermore, it must be kept in mind that the frequent use of antiseptics may also exert some negative effects such as inducing potentially detrimental ecological shifts in the oral microbiota ( Mao et al 2022 ) or development of antiseptic resistance in oral bacteria ( Verspecht et al 2019 ; Auer et al 2022 ; Muehler et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we recently showed that twice-daily treatment of microcosm biofilms with CHX led to an ecological shift toward Gram-positive cocci in these biofilms. [ 19 ]. S. oralis was reported to have lower environmental requirements for a high growth rate in combination with a high adherence ability [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Mao et al recently showed that multi-resistant phenotypes with additional resistance to CHX could be isolated from microcosm biofilms that were cultured in vitro and subjected to antiseptic treatment twice daily [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, further work is needed to establish the link between the observed reduction in viral infectivity from CPC-containing mouthwashes and a clinically useful reduction in the risk of transmission of SARS-CoV-2. Ultimately, large-scale clinical studies will be needed to address this issue and identify the optimal approaches for delivering CPC or other antiseptics, while considering potentially detrimental ecologic shifts in the oral microbiota that may result from regular antiseptic use (Bescos et al 2020; Mao et al 2022).…”
mentioning
confidence: 99%
“…Ultimately, large-scale clinical studies will be needed to address this issue and identify the optimal approaches for delivering CPC or other antiseptics, while considering potentially detrimental ecologic shifts in the oral microbiota that may result from regular antiseptic use ( Bescos et al. 2020 ; Mao et al 2022 ).…”
mentioning
confidence: 99%